2013
DOI: 10.1177/193229681300700516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Point-of-Care Blood Glucose Measurements in Patients with Diabetic Ketoacidosis or Hyperglycemic Hyperosmolar Syndrome Admitted to a Critical Care Unit

Abstract: Background: Point-of-care (POC) blood glucose (BG) measurement is currently not recommended in the treatment of patients presenting with diabetic ketoacidosis (DKA) or hyperglycemic hyperosmolar syndrome (HHS). Methods: We prospectively evaluated and compared capillary and venous POC BG values with laboratory venous glucose in patients with DKA or HHS admitted to one critical care unit over 8 months. Results: Venous laboratory glucose was strongly correlated with venous (r = 0.98) and capillary (r = 0.96) POC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A recent study indicated that venous blood POC error was not considered clinically significant in patients with DKA/HHS. 27 The authors concluded that there is a low risk of causing hypoglycemia from excess insulin administration based on POC glucose error but stated that patient harm could occur by delaying correction of metabolic disturbances in patients with DKA/HHS. Therefore further investigation is required to determine if POC BHB methods affected by hematocrit will influence the management of ketonemia particularly in patients following a goal directed targeted treatment for DKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study indicated that venous blood POC error was not considered clinically significant in patients with DKA/HHS. 27 The authors concluded that there is a low risk of causing hypoglycemia from excess insulin administration based on POC glucose error but stated that patient harm could occur by delaying correction of metabolic disturbances in patients with DKA/HHS. Therefore further investigation is required to determine if POC BHB methods affected by hematocrit will influence the management of ketonemia particularly in patients following a goal directed targeted treatment for DKA.…”
Section: Discussionmentioning
confidence: 99%
“…In the NICU study 37 abnormal levels of pH and electrolytes were also assessed and shown not to influence the accuracy of StatStrip. In a recent study it was reported that Accu-Chek POC glucose accuracy was influenced by acidemia, which can be present in DKA/HHS patients, 27 and as such further investigation into the role of fluctuating pH ranges on POC meter performance is required.…”
Section: Discussionmentioning
confidence: 99%
“…Preanalytical variables, common in the ICU, fall into three core groupings: the user interface-including the user skills, device-specific, and technique used for specimen collection; patient/therapy factors-such as interfering medication or endogenous substances; and physiologic, reflecting glucose metabolism, capillaryto-plasma glucose gradients, insulin kinetics, and more. Further inaccuracy may result from slow glucose equilibration during hypotension or shock (124), with vasopressors (125), or other states of impaired microcirculation, edema, acidosis, dehydration, and extremes of glucose values (126)(127)(128)(129).…”
Section: Adult and Pediatric Glucose Monitoring Devicesmentioning
confidence: 99%
“…Volume status (including fluid intake and output), vital signs, neurological status, plasma concentrations of electrolytes, anion gap, osmolality and glucose need to be monitored closely, initially as often as every 2 hours (1,31,32). Capillary blood glucose (CBG) measurements are unreliable in the setting of severe acidosis (46). Precipitating factors must be diagnosed and treated (1,31,32).…”
Section: Managementmentioning
confidence: 99%